Stochasticity and the limits of molecular signaling in plant development - Lintilhac, Philip M. (Frontiers in Plant Science, 2022)
Understanding plant development is in part a theoretical endeavor that can only succeed if it is based upon a correctly contrived axiomatic framework. Here I revisit the basic assumptions that frame our understanding of plant development and propose that we consider an alternative informational ecosystem that more faithfully reflects the physical and architectural realities of plant tissue and organ growth. I discuss the limits of molecular signaling as a stochastic process and propose that the iterative and architectural nature of plant growth is more usefully represented by a deterministic model based upon structural, surficial, and stress-mechanical information networks.